Variação sazonal dos componentes da alga marinha vermelha Gracilaria birdiae (Plastino & Oliveira) - Pereira, Juliana Gomes (2009)
Seaweeds are classified in the kingdom protist, predominantly aquatic and with great adaptive capacity. Found in all regions of the planet, algae play an important role ecological and economic, representing a great potential for bioresources. The red seaweed Gracilaria birdiae, collected during twelves months, was submitted to aqueous extraction of polysaccharides at 100ºC, showed yield exceeding 50 %, except in February, September and November 2007 (49,5%, 41,8% and 49,4% respectively). The sulfate content was obtained by microanalysis and it not vary significantly over the months examined averaging 1,35%. The sulfate degree was 0.15. The protein content in the samples also showed no considerable variation, with average of 0,5%, howevwr in April, the protein content increased about 3 times the average found. The twelve samples were chemically characterized by Gel Permeation Chromatography (GPC), Infrared (FT-IR) and Nuclear Magnetic Resonance (NMR) spectroscopy. The GPC chromatograms of the samples showed similarity and typical characteristics of polysaccharides from red algae. In general, we observed a main peak, at approximately 9,2 mL volume of eluition, with the exception of August, October and November 2007, which showed chromatograms with main peak at approximately 8,7 mL volume of eluition, detected by a refractive index. The polysaccharides investigated showed hight molecular weight, ranging from 0.11 x 104 and 8.51 x 105 g/mol. The infrared spectra of the twelve samples of polysaccharides presented similar profiles, with bands characteristics of agarocolloids, more specifically agaran-like, with evidence of protein. NMR were employed to the structural characterization of the samples throughout the year and revealed that the structure of polysaccharides is composed by (1→3)-β-D-galactopyranosyl linkage to (1→4)-α-L-anhydrogalactopyranosyl segments. The study of seasonal variation in proximate composition, in general, showed no marked variation. Regarding the amount of soluble protein in the crude extract, the study of seasonal variation showed a small variation in the content of soluble protein, with maximum value (0,94 mgP/mL) in November/06 and minimum (0,39 mgP/mL) in December/06. The hemagglutinating activity during the period of one year, except in December/06.